DIFFERENTIAL EQUATIONS SYSTEMS AND COORDINATE SYSTEMS - MACUROVA, Anna; MACURA, Dusan (Trends in education, 2008)
The article introduces some coordinate systems important for transformation nonlinear differential equations system and investigated the properties of the solutions. The nonlinear differential equations systems are investigated as quasilinear differential equations systems.
Keywords: Differential equations systems; coordinates systems; transformation systems.